2019
DOI: 10.1002/ca.23405
|View full text |Cite
|
Sign up to set email alerts
|

Does three‐dimensional anatomy improve student understanding?

Abstract: We aim to provide an overview of the various digital three‐dimensional visualizations used for learning anatomy and to assess whether these improve medical students' understanding of anatomy compared to traditional learning methods. Furthermore, we evaluate the attitudes of the users of three‐dimensional visualizations. We included articles that compared advanced newer three‐dimensional anatomy visualization methods (i.e., virtual reality, augmented reality, and computer‐based three‐dimensional visualizations)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
103
0
6

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(132 citation statements)
references
References 38 publications
5
103
0
6
Order By: Relevance
“…The students who were taught via the first two methods achieved significantly better examinations scores than the students who were taught via the third method. These results agree with the finding of a recent systematic review of the literature (Triepels et al, 2020), according to which 3D visualization technologies are superior to traditional methods regarding acquisition of anatomical knowledge. Also, 3D printing technology has been demonstrated as significantly more effective anatomy education method than prosected cadaveric skulls, according to the randomized controlled trial by Chen et al (2017).…”
Section: Is Cadaveric Dissection the "Gold Standard" For Neuroanatomysupporting
confidence: 92%
“…The students who were taught via the first two methods achieved significantly better examinations scores than the students who were taught via the third method. These results agree with the finding of a recent systematic review of the literature (Triepels et al, 2020), according to which 3D visualization technologies are superior to traditional methods regarding acquisition of anatomical knowledge. Also, 3D printing technology has been demonstrated as significantly more effective anatomy education method than prosected cadaveric skulls, according to the randomized controlled trial by Chen et al (2017).…”
Section: Is Cadaveric Dissection the "Gold Standard" For Neuroanatomysupporting
confidence: 92%
“…It is evident that given the attitude and mindset of the “YouTube generation,” in addition to the educational benefits of 3DVT software has on knowledge acquisition, the field of anatomy education needs to integrate 3DVT learning resources into anatomy courses to improve student learning outcomes. Two recent systematic reviews evaluating the effectiveness of 3DVT anatomy learning tools showed that 3DVT teaching tools improve spatial structure recognition, factual knowledge, and thus examination scores (Yammine and Violato, 2015; Triepels et al, 2020). In addition, a common conclusion of these two reviews demonstrated that most students report they will continue to use 3DVT enhanced anatomy technology because it is more enjoyable than traditional two‐dimensional material in textbooks (Yammine and Violato, 2015; Triepels et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Two recent systematic reviews evaluating the effectiveness of 3DVT anatomy learning tools showed that 3DVT teaching tools improve spatial structure recognition, factual knowledge, and thus examination scores (Yammine and Violato, 2015; Triepels et al, 2020). In addition, a common conclusion of these two reviews demonstrated that most students report they will continue to use 3DVT enhanced anatomy technology because it is more enjoyable than traditional two‐dimensional material in textbooks (Yammine and Violato, 2015; Triepels et al, 2020). Hence, it can be hypothesized that the incorporation of 3DVT materials into anatomy courses might be a great teaching strategy to improve retention of URM students in academic healthcare programs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study which evaluated the use of augmented reality in dental anatomy education failed to prove that this 3D visualization technology could be considered as a better teaching tool than cadavers (Zafar and Zachar, 2020). The aforementioned findings do not agree with the conclusion of a recent systematic review of the literature (Triepels et al, 2020), according to which 3D visualization technologies are more effective means of obtaining anatomical knowledge, in comparison with traditional modalities.…”
mentioning
confidence: 84%